PERANAN FINANCIAL LITERACY TERHADAP PERILAKU PETANI DALAM MENGELOLA KEUANGAN (Studi pada Petani Desa Semamung) - Anwar SA (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
This study aims to determine the effect of financial literacy on the behavior of farmers in Semamung Village, Moyo Hulu District in managing their personal finances. This research uses quantitative methods. The sample in the study amounted to 50 respondents obtained with a nonprobability sampling design with purposive sampling technique. The population in this study were the people of Semamung village, Moyo Hulu sub-district who work as farmers. The data collection technique in this study used a questionnaire technique. Data analysis techniques in this study used Classical Assumption Test, Simple Linear Regression, Hypothesis Test (T Test) and Coefficient of Determination. Data processing in this study used the SPSS version 24 software program. Financial literacy has a significant effect on financial management behavior among farmers in Semamung Village, Moyo Hulu District. This is based on the value of the financial literacy variable (X) is 7.533 with a significant level of 0.000 because tcount is greater than ttable, namely 7.533 ≥ 1.984 and a significance value of 0.000 ≤ 0.05. Thus the results of the data analysis show that Ha is accepted and Ho is rejected, so it can be stated that financial literacy has a significant effect on financial management behavior among farmers in Semamung Village, Moyo Hulu District.